The application of metabolomics toward idiopathic pulmonary fibrosis and potential metabolomic value of diverse samples in interstitial lung diseases - Mingtao Liu; Zhangkai J. Cheng; Mingshan Xue; Runpei Lin; Teng Zhang; Baoqing Sun (Precision Medical Sciences, 2023)
Abstract Interstitial lung diseases (ILDs), also known as diffuse lung diseases, pose a significant challenge to the respiratory health of individuals worldwide. Among these conditions, idiopathic pulmonary fibrosis (IPF) is one of the most prevalent, contributing substantially to morbidity and mortality. However, IPF is characterized by high heterogeneity, presenting a substantial obstacle to clinical program development and scientific research due to significant variations in disease progression, treatment response, and prognosis. Recent advances in metabolomics have enabled the identification of specific biochemical pathways and disease biomarkers, offering a beacon of hope for patients afflicted with various diseases. Remarkably, metabolomics has made significant strides in ILDs, particularly in IPF. Metabonomics, a branch of life science, provides an in‐depth analysis of metabolic pathways and the specific biological molecular composition of omics, obtained primarily from biological samples such as serum, plasma, pleural effusion, bronchoalveolar lavage fluid, lung surgical biopsy samples, urine, feces, sputum, and cerebrospinal fluid. In this review, we aim to provide a comprehensive overview of the application of metabolomics in ILDs, with a particular focus on IPF. By summarizing the current state of research in this field, we hope to shed light on the latest advances, challenges, and opportunities that metabolomics can provide in managing ILDs.